Perbaikan dan Penentuan Critical Point SOP Sales Order - Rivan Setiawan Sudiro; I Nyoman Sutapa (Jurnal Titra, 2015)
PT X is a chemical manufacturer, which has ISO 9001:2008 certified. However, there is no time limit and explicit documents references on each department in PT X. Additionally, the critical points of the current procedures are also not yet specified, so that it is difficult to determine which activities are important to be implemented. Therefore, this research aims are improving and determining the critical points on each operating procedure, i.e. sales order, purchasing, customer complaint, and customer satisfaction. The research is conducted through observation and interviews. As the results, now the time limit of each operating procedure is clear, the required documents are explicitly written, and the critical points are specified.